IMPROVING STUDENTS' SPEAKING ABILITY BY USING ROLE- PLAY AT PHARMACY MAJOR OF HEALTH POLYTECHNIC PALEMBANG - LILIS MARYANTI (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2017)
The objectives of this study to identify whether the use of roleplay was effective to improve the students' speaking ability at Pharmacy Major of Health Polytechnic Palembang.The study applied experimental method and used non-equivalent control design The population were 60 students of Pharmacy Poltekkes Kemenkes Palembang. They were grouped into two groups as the experimental and contol group. The test was administred twice as pre-test and post-test. The results of the test were analyzed by using t-test through SPSS (Statistical Package for Social Sciences) program. The results of the study showed that there was a significant difference in speaking ability between the students of Pharmacy Poltekkes Kemenkes Palembang who were taught by using role-play and those who were not based on the independent sample t-test, and role-play has an effect to the student's ability.